Application of laser backscattering imaging for the physico-chemical characterisation of antimicrobial silica particles functionalised with plant essential oils. (September 2020) - Verdú, Samuel; Ruiz-Rico, Maria; Pérez, Alberto J.; Barat, José M.; Grau, Raúl
Abstract: The capacity of orthogonal imaging applied to laser-backscattering for characterising antimicrobial particles based on immobilised essential oils was tested. Different particles were synthesised using various particle and oils. Samples were characterised physico-chemically and by an imaging technique. The technique recorded the generated patterns because of the laser-particles interaction during the sedimentation process. The series of images were transformed into an orthogonal image. Data extraction varied depending on the fragmentation degree of image length. After the multivariate analysis, the physico-chemical results showed variability due to particle size. That variability diminished the effect of oils for large sizes. The imaging data collected these properties, which could be used to recognise both particle size and oil type. Thus the prediction of the properties was successful. The position in the physico-chemical space of variance was also predicted. Hence this technique could complement a low-cost method to evaluate the properties of functionalised particles with oils.